Using the Mistake Buster Technique to Improve the English Grammar Mastery - Andi Tenrisanna Syam (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
This research aims at finding out whether or not the use of mistake buster technique is able to improve the English grammar mastery and finding out the students’ interest toward the use of mistake buster technique. The research employs a quasi-experimental research method. The population and sample consist of 66 students which belong to two groups; 33 students in experimental group and 33 students in control group. The research data are collected using grammar test and questionnaire which are analyzed by inferential and descriptive statistics through SPSS 17.0 and Likert Scale. The research result indicates that the use of mistake buster technique is more effective than non-mistake buster technique in improving English grammar mastery of the ten grade students of SMA Negeri 3 Makassar in academic year 2014/2015. The students’ result of posttest for experimental group is higher than the students’ result of posttest for control group. It is proven by the mean score of posttest of experimental group is higher than the control group in grammar test (63.87 > 40.00). The difference of those mean score is statistically significant; it is based on t-test value at significant level 0.05, the probability value is lower than significant level (0.00 < 0.05). Then, analysis using Likert Scale shows that the students’ interested to learn grammar by using mistake buster technique. It is proved by 60.6% students were in very interested category.